Occupational exposure in swine farm defines human skin and nasal microbiota - Wang, Xiran; Chen, Dongrui; Du, Juan; Cheng, Ke; Fang, Chang; Liao, Xiaoping; Liu, Yahong; Sun, Jian; Lian, Xinlei; Ren, Hao (Frontiers in Microbiology, 2023)
Anthropogenic environments take an active part in shaping the human microbiome. In a previous study, we studied the impact of occupational exposure on gut microbiome in confined and controlled swine farms. Here in the present study, we extended our focus to decipher the skin and nasal microbiota dynamic in response to the exposure in the swine farms. By longitudinally surveying the microbiota of volunteers before, during and after internship in swine farms, we showed that the occupational exposure compositionally and functionally reshaped the skin and nasal microbiota. The exposure in different farms resulted in the different microbial patterns. The exposure in farm A reduced the microbial diversity of skin and nasal microbiota, which was observed to increase after exposure in farm B. The remodeled microbiota composition due to exposure in farm A appeared to stall and persist, whereas the microbiota of volunteers in farm B showed better resilience to revert to pre-exposure state after the internship. Several metabolic pathways were significantly altered through our PICRUSt analysis, and notably, the function of beta-lactam resistance was predicted to enrich after exposure in farm A yet decrease in farm B. We proposed that the differently modified microbiota patterns might be coordinated by microbial and non-microbial factors in different swine farms, which were always environment-specific. This study shed the light on the active role of occupational exposure in defining the skin and nasal microbiota and the logical next step will be deciphering the relevance of changes with environmental cues for providing more in-depth understandings.